FINANCIAL INCLUSION OF THE ISLANDS REGION: CREATING A POVERTY-FREE SOCIETY - Mohammad H. Holle; Abdul Rauf Wajo; La Ode Masri; Dewi Fatmala Umagap (Department of Islamic Accounting, The Faculty of Islamic Economics and Business, State Islamic Institute of Kediri [IAIN Kediri, 2024)
Abstract: This study aims to examine the financial inclusion program in the Indonesian archipelago and its impact on poverty alleviation. This study uses a descriptive qualitative research method by reviewing the real lives of people living in the archipelago in Indonesia using secondary sources related to the single problem of this study, namely financial inclusion in the archipelago as an effort to free people from the trap of poverty as the goal of the SDGs. Access indicators are the main focus of this study. This study found that financial inclusion programs targeting people living in the archipelago in Indonesia are not optimal. The causes are the lack of socialization of financial inclusion, literacy and inclusion targets that are still limited to urban communities, geographical constraints, limited transportation, and of course the lack of financial institution infrastructure, both banks and non-banks, both formal and informal, which makes people in the archipelago lose access. Abstrak: Penelitian ini bertujuan untuk mengkaji program inklusi keuangan di kepulauan Indonesia dan dampaknya terhadap pengentasan kemiskinan. Penelitian ini menggunakan metode penelitian kualitatif deskriptif dengan mengkaji kehidupan nyata masyarakat yang tinggal di daerah kepulauan di Indonesia dengan menggunakan sumber-sumber sekunder yang berkaitan dengan masalah tunggal penelitian ini, yaitu inklusi keuangan di daerah kepulauan sebagai upaya membebaskan masyarakat dari jerat kemiskinan sebagai tujuan SDGs. Indikator akses menjadi fokus utama dalam penelitian ini. Studi ini menemukan bahwa program inklusi keuangan yang menyasar masyarakat yang tinggal di daerah kepulauan di Indonesia belum optimal. Penyebabnya adalah kurangnya sosialisasi inklusi keuangan, target literasi dan inklusi yang masih terbatas pada masyarakat perkotaan, kendala geografis, transportasi yang terbatas, dan tentu saja minimnya infrastruktur lembaga keuangan, baik bank maupun non-bank, baik formal maupun informal, yang membuat masyarakat di daerah kepulauan tidak memiliki akses.